Assessment of Cybersecurity Challenges and Their Implications for National Security in Nigeria - Nura Umar Manya Manya; Isah Maina (Penerbit Hellow Pustaka, 2026)
The rapid expansion of Nigeria's digital ecosystem has transformed cybersecurity from a technological concern into a critical component of national security. As government institutions, financial systems, telecommunications, education, healthcare, and other critical infrastructure increasingly rely on digital technologies, the country has become more vulnerable to cyber threats. This study assessed the cybersecurity challenges facing Nigeria and examined their implications for national security. A qualitative descriptive research design based on documentary analysis was adopted. Data were obtained from secondary sources, including peer-reviewed journal articles, books, government publications, policy documents, and reports from national and international organizations. The collected data were analyzed using qualitative content analysis. The findings revealed that Nigeria continues to face diverse cybersecurity threats, including phishing, ransomware, business email compromise, identity theft, cyber fraud, cyber-enabled terrorism, misinformation, and attacks on critical national infrastructure. These threats undermine economic stability, weaken institutional resilience, threaten public safety, and compromise national sovereignty. The study further found that weak cybersecurity governance, inadequate funding, limited institutional capacity, shortage of skilled cybersecurity professionals, poor public cyber awareness, and insufficient inter-agency collaboration remain major barriers to effective cybersecurity management. The study also established that emerging technologies, particularly Artificial Intelligence (AI), offer significant opportunities for strengthening cybersecurity through automated threat detection, predictive analytics, anomaly detection, biometric authentication, malware identification, and real-time incident response. However, the misuse of AI by cybercriminals for sophisticated phishing attacks, deepfakes, automated malware, and intelligent cyberattacks presents new security challenges that require effective regulation and ethical governance. The analysis was anchored on Systems Theory, National Security Theory, and Deterrence Theory, which collectively explain the interconnected nature of cyberspace, the responsibility of government to protect national digital assets, and the importance of strong legal and institutional measures in preventing cybercrime. The study concludes that cybersecurity has become indispensable to Nigeria's national security and sustainable development. It recommends increased investment in AI-enabled cybersecurity technologies, effective implementation of the National Cybersecurity Policy and Strategy and the Cybercrimes (Prohibition, Prevention, etc.) Act, 2015, continuous capacity building for cybersecurity professionals, enhanced public awareness, stronger inter-agency coordination, and greater international cooperation. Implementing these measures will improve Nigeria's cyber resilience, protect critical national infrastructure, strengthen national security, and support sustainable socio-economic development in the digital age.